Numerical analysis of metal powder under loading / M. M. Rahman, S. S. M. Nor and A. K. Ariffin - Rahman, M. M.; Nor, S. S. M.; Ariffin, A. K. (2004)
The coupled mechanical ,and thermal analysis of powder during the warm compaction process has been studied. This paper presents the development of the finite element model for the simulation of warm metal powder compaction process. In the modelling, the behaviour of powder is assumed to be rate independent thermo-elastoplastic material. The material constitutive laws are derived based on a continuum mechanics approach. The deformation process has been described by a large displacement based finite element formulation. Three constitutive relations namely Mohr Coulomb yield model, Elliptical Cap yield model, and the combination of these two have been used to describe the deformation behaviour of the powder mass during the compaction process. These yield models were tested, however an Elliptical Cap model was shown to be the most appropriate to represent the compaction process. The staggered-incremental-iterative solution strategy has been established to solve the non-linearity in the systems of equations. The numerical simulation results were validated against the experimental data, where a good agreement was found between the numerical simulation results and the experimental data.